Passiflora edulis Sims (passion fruit) leaves methanol extract toxicity in rats - Rojas, Juan (2009)
Objective: To determine oral toxicity of Passiflora edulis leaves methanol extract repeated doses in rats. Design: Experimental study. Setting: Institute of Clinical Research and Institute of Pathology, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological material: Adult female and male albino rats, and Passiflora edulis leaves. Methods: Passiflora edulis leaves harvested in Trujillo were dried at 38° C, powdered and macerated with methanol, filtered, concentrated and lyophilized. Two 10 rats (5 per sex) experimental groups were formed. One group was control that received distilled water and the other was the treated group that received Passiflora edulis leaves methanol extract in doses of 200 mg/kg once/day orally for 28 days. Clinical observations were done daily and the animals were weighed each week. At the end of the experiment we performed hematological, clinical biochemistry determinations and histology. Organs were extracted for determination of weight and histopathological study. Main outcome measures: Body weight, hematologic indicators, biochemical and histological analysis. Results: There was no mortality or clinical and hematological abnormalities. Alanine aminotransferase increased very slightly to 55,4 ± 4,9 U/L in males (VN = 35,1-53,5) and 53,8 ± 3,9 U/L (VN = 28,8-46,0) in females. Histopathology revealed one case of focal hepatocytes microvesicles and two cases of renal tubular necrosis foci. Conclusions: Repeated oral dose administration of Passiflora edulis leaves methanol extract in rats for 28 days is not toxic.